Strategi Peningkatan Minat Generasi Muda Bekerja Disektor Pertanian di Kabupaten Kolaka Utara - Rahman, Rahman; Suryanto, Suryanto; Dewi Maryeti; Ahmad, Ahfandi (Tarjih : Agribusiness Development Journal, 2025)
This study aims to develop strategies to increase the interest of young farmers in Rante Angin District, North Kolaka Regency, through a SWOT analysis. Data were collected from 20 young farmer respondents aged 15–35 years old using observation, interviews, questionnaires, and literature review. The analysis results indicate a strategic position in Quadrant I (aggressive strategy) with an IFAS score of 3.93 and an EFAS score of 3.67, indicating strong internal strengths and significant external opportunities. Government programs such as Millennial Farmers, People's Business Credit (KUR), technical training, digital market development, organic product certification, private sector partnerships, and smart farming technology are key factors that can encourage youth involvement in the agricultural sector. Recommended strategies include optimizing government programs, increasing youth capacity, developing digital marketing, and positive campaigns to change negative perceptions of agriculture. This study provides basic strategies to support the regeneration of young farmers and increase the competitiveness of sustainable agriculture.